The Effectiveness of Physical Exercise on the Quality of Life of Elderly Patients with Osteoarthritis at Sekip Public Health Center, Palembang - nurjannah; Saryanto (Holistic Nursing Plus, 2026)
Background: Osteoarthritis is a degenerative joint disease that commonly affects the elderly and may lead to pain, physical limitations, and decreased quality of life. Regular physical activity is considered one of the non-pharmacological interventions that can help improve the physical and psychological well-being of older adults with osteoarthritis. Purpose: This study aimed to determine the effectiveness of physical exercise on the quality of life of elderly individuals with osteoarthritis at Sekip Health Center, Palembang. Methods: This study used a quantitative approach with a pre-experimental design using a one-group pretest–posttest design. The study involved 30 elderly respondents with osteoarthritis selected using a total sampling technique. Quality of life was measured using the World Health Organization Quality of Life (WHOQOL-BREF) questionnaire consisting of 26 items. The intervention was a physical exercise program conducted for 30 minutes, three times per week. Data analysis included univariate and bivariate analyses. The normality test was performed using the Shapiro–Wilk test, and the hypothesis was tested using the paired sample t-test with a significance level of 0.05. Results: The results showed that before the intervention most respondents had poor quality of life (66.7%), while 33.3% had moderate quality of life. After the physical exercise intervention, the majority of respondents had moderate quality of life (73.3%), 20% had good quality of life, and only 6.7% had poor quality of life. The mean quality of life score increased from 61.10 before the intervention to 79.17 after the intervention, with an average difference of 18.7 points. The paired sample t-test showed a significant effect of physical exercise on quality of life (p = 0.000 < 0.05). Conclusions: Physical exercise is effective in improving the quality of life of elderly individuals with osteoarthritis. Regular and structured physical activity programs are recommended as a non-pharmacological intervention to enhance physical, psychological, and social well-being among the elderly.